Neurocognitive function in HIV infected patients on antiretroviral therapy. - Alan Winston; Alejandro Arenas-Pinto; Wolfgang Stöhr; Martin Fisher; Chloe M Orkin; Kazeem Aderogba; Andrew De Burgh-Thomas; Nigel O'Farrell; Charles Jn Lacey; Clifford Leen; David Dunn; Nicholas I Paton; et al. (PLoS ONE)
Objective To describe factors associated with neurocognitive (NC) function in HIV-positive patients on stable combination antiretroviral therapy. Design We undertook a cross-sectional analysis assessing NC data obtained at baseline in patients entering the Protease-Inhibitor-Monotherapy-Versus-Ongoing-Triple therapy (PIVOT) trial. Main outcome measure NC testing comprised of 5 domains. Raw results were z-transformed using standard and demographically adjusted normative datasets (ND). Global z-scores (NPZ-5) were derived from averaging the 5 domains and percentage of subjects with test scores >1 standard deviation (SD) below population means in at least two domains (abnormal Frascati score) calculated. Patient characteristics associated with NC results were assessed using multivariable linear regression. Results Of the 587 patients in PIVOT, 557 had full NC results and were included. 77% were male, 68% Caucasian and 28% of Black ethnicity. Mean (SD) baseline and nadir CD4+ lymphocyte counts were 553(217) and 177(117) cells/µL, respectively, and HIV RNA was <50 copies/mL in all. Median (IQR) NPZ-5 score was -0.5 (-1.2/-0) overall, and -0.3 (-0.7/0.1) and -1.4 (-2/-0.8) in subjects of Caucasian and Black ethnicity, respectively. Abnormal Frascati scores using the standard-ND were observed in 51%, 38%, and 81%, respectively, of subjects overall, Caucasian and Black ethnicity (p<0.001), but in 62% and 69% of Caucasian and Black subjects using demographically adjusted-ND (p = 0.20). In the multivariate analysis, only Black ethnicity was associated with poorer NPZ-5 scores (P<0.001). Conclusions In this large group of HIV-infected subjects with viral load suppression, ethnicity but not HIV-disease factors is closely associated with NC results. The prevalence of abnormal results is highly dependent on control datasets utilised. Trial registry ClinicalTrials.gov, NCT01230580.